Experimental Success in Marburg Virus Vaccination - Dydyk, Martyna; Nowak, Aleksandra (Quality in Sport, 2024)
The Marburg virus (MRV), classified within the Filoviridae family, was initially identified in 1967, precipitating Marburg virus disease (MARV), a severe and often fatal hemorrhagic fever. With its pronounced infectiousness, high mortality rate, and proclivity for epidemic outbreaks, MARV stands as a formidable public health menace. Despite extensive sporadic outbreaks and its designation as a priority disease, the quest for efficacious drugs or vaccines against MRV remains an ongoing challenge. Nonetheless, the relentless pursuit of scientific inquiry, augmented by the innovative application of immunoinformatics, is propelling forward vaccine development endeavors. Current vaccine candidates, spanning from VSV-based formulations to virus-like particle vaccines, exhibit encouraging outcomes in preclinical and clinical evaluations, boasting notable efficacy and safety profiles. Furthermore, the exploration of multivalent vaccine strategies, designed to target a spectrum of hemorrhagic fever viruses, holds promise in fortifying pandemic preparedness efforts. Immunoinformatics assumes a pivotal role in this context, offering predictive insights into vaccine candidate selection and optimization, thereby facilitating expedited development tailored to diverse demographic cohorts. The integration of computational modeling techniques into vaccine development paradigms represents a transformative avenue for effectively controlling MRV outbreaks on a global scale. Sustained collaboration and continued research endeavors are imperative to fully harness the potential of these advancements in confronting the formidable challenge posed by the lethal Marburg virus and safeguarding global public health.